Technical competencies of medical and health librarians in a library 2.0 environment - Yap, Joseph M. (School of Library and Information Studies, University of the Philippines Diliman, 2010)
Fifty-one medical and health librarians were interviewed and surveyed in five (5) regions of Luzon. The regions represented were NCR, CAR, Region I, Region III and Region IV-A. Five types of medical and health libraries were also considered for this research: hospital library, academic health science library, specialty health-related library, corporate health-related library and a medical/health government library.